Can't be Overlooked: A Case Report of Pansinusitis Causing a Rare and Life-Threatening Cavernous Sinus Thrombosis - Theresa Puspanadi; Paulus Sugianto; Edward Limantara; Teguh Filbert Metaputra (Riviera Publishing, 2025)
Sinusitis is a prevalent, mostly favorable medical condition. However, in rare cases, inadequately treated sinusitis can lead to devastating and life-threatening complications, such as cavernous sinus thrombosis (CST). We present the case of a 41-year-old woman presenting with diplopia and ophthalmoplegia, ptosis, facial paresthesia, and less common facial paresis. Diagnostic imaging–including magnetic resonance imaging (MRI), magnetic resonance angiography (MRA), and digital subtraction angiography (DSA) confirmed bilateral CST secondary to untreated pansinusitis. Cultures of sinus drainage revealed uncommon pathogens: Staphylococcus epidermidis and Chryseobacterium indologenes. A multidisciplinary approach involving intravenous antibiotics, anticoagulation, and functional endoscopic sinus surgery (FESS) resulted in significant clinical improvement. This case highlights the critical need for accurate diagnosis, timely and prudent intervention, and enhanced public health education to prevent potentially life-threatening complications of untreated sinusitis. Moreover, it contributes novel insights into the atypical microbiological profile and neurological manifestations of CST.